2007
DOI: 10.1038/nprot.2007.405
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric analysis of cells with different mitochondrial membrane potential during apoptosis by polychromatic flow cytometry

Abstract: The analysis of changes in mitochondrial membrane potential (MMP) that can occur during apoptosis provides precious information on the mechanisms and pathways of cell death. For many years, the metachromatic fluorochrome JC-1 (5,5',6,6'-tetrachloro-1,1',3,3'-tetraethylbenzimidazolcarbocyanine iodide) was used for this purpose. Thanks to new dyes and to the technical improvements recently adopted in several flow cytometers, it is now possible to investigate, along with MMP, a variety of other parameters. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 45 publications
3
106
0
Order By: Relevance
“…Hoechst 33342 staining was performed as described earlier (19), and cells were analyzed using the CyFlow ML (Partec GmbH, Muenster, Germany) cytofluorimeter. Cells were stained with TO-PRO3 vital dye (Molecular Probes) before analysis as described previously (60). Immunofluorescence was carried out as described by Kilstrup-Nielsen et al (30), and stained cells were observed with a Zeiss AxioSkop 40 fluorescence microscope (Carl Zeiss, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Hoechst 33342 staining was performed as described earlier (19), and cells were analyzed using the CyFlow ML (Partec GmbH, Muenster, Germany) cytofluorimeter. Cells were stained with TO-PRO3 vital dye (Molecular Probes) before analysis as described previously (60). Immunofluorescence was carried out as described by Kilstrup-Nielsen et al (30), and stained cells were observed with a Zeiss AxioSkop 40 fluorescence microscope (Carl Zeiss, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To study mitochondrial function before cell death, assays evaluating mitochondria were performed after 6 hours of 125 mmol/L H 2 O 2 treatment. The JC-1 assay is a well accepted method of studying MMP (31).…”
Section: Autophagic Protein-depleted Mscs Show Increased Susceptibilimentioning
confidence: 99%
“…On the other hand, in apoptotic or unhealthy cells with low MMP, JC-1 remains in the monomeric form, which shows only green fluorescence. The ratio of Red/Green represents the amount of healthy cells [27] .…”
Section: Wwwchinapharcom Wu LX Et Almentioning
confidence: 99%